2015
DOI: 10.14486/ijscs265
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesi̇ Dönem Çocuklarinin Spora İli̇şki̇n Görüşleri̇ni̇n İncelenmesi̇

Abstract: Bireylerin erken yıllardan itibaren spor ile tanışması, onların gelecek yaşamlarında spora ilişkin tutum ve davranışlarının önemli bir belirleyicisidir. Erken çocukluk dönemi ise, çocukların gelişimlerinin desteklenmesi yanında belli bazı alışkanlıkların kazandırılmasında önemli bir zaman dilimidir. Bu nedenle bu araştırmada, okul öncesi dönem çocuklarının spora ilişkin görüşlerini ve beklentilerini belirlemek amaçlanmıştır. Çalışma grubunu, anaokuluna devam eden 3-6 yaş grubundan 24 çocuk oluşturmuştur. Nitel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
4
0
2
Order By: Relevance
“…In a study done by Tezel Şahin & Yüksek Usta (2016) [9] to determine pre-school children's perceptions of sports and sports branches, it was found that the participating children prefer running, football, ice skating, weightlifting, fencing, bowling, baseball, and basketball. Aydoğan, Özyürek & Gültekin Akduman (2015) [13] found that in general the sports branches the children want to be engaged in are football, skating and gymnastics. Huck, Hefler, Hickman and Kiefer (2001) [24], reported that particularly the books addressing the sports branches that can be performed individually or in groups such as tennis, running, gymnastics, skiing, swimming, football and basketball enhance and enrich the children's sports-related experiences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study done by Tezel Şahin & Yüksek Usta (2016) [9] to determine pre-school children's perceptions of sports and sports branches, it was found that the participating children prefer running, football, ice skating, weightlifting, fencing, bowling, baseball, and basketball. Aydoğan, Özyürek & Gültekin Akduman (2015) [13] found that in general the sports branches the children want to be engaged in are football, skating and gymnastics. Huck, Hefler, Hickman and Kiefer (2001) [24], reported that particularly the books addressing the sports branches that can be performed individually or in groups such as tennis, running, gymnastics, skiing, swimming, football and basketball enhance and enrich the children's sports-related experiences.…”
Section: Discussionmentioning
confidence: 99%
“…In the pictures where outdoor activities are depicted, green areas and clear air are shown. In a study by Aydoğan, Özyürek & Gültekin Akduman (2015) [13], it was found that the children responded to the question "Where is sports done?" as generally at home or outside.…”
Section: Discussionmentioning
confidence: 99%
“…Games played as a child existed on a different side of the sport. In this way, it is an argument used in education and health with various games and movements for the development of children (Aydoğan et al, 2015). Sport has universal characteristics, regardless of any distinction that unites all classes.…”
Section: Introductionmentioning
confidence: 99%
“…Sport is a professionally chosen area that is preferred for the needs of the individual to meet, play, cheer, socialize, get status and for many other reasons; it is all of the body movements that are made in personal or collective form and are usually applied to certain rules, which are based on competition (3,14,26). Sport gives a healthy life style to the individuals from all ages, and protective tibbles have begun to take place in our lives again by creating alternative sources.…”
Section: Introductionmentioning
confidence: 99%